Legal Review of The Criminal Act of Murder of Women By Intimate Partners Based on The Provisions of The Act on PKDRT - Chrishans, Raffael Moreno; Firmansyah, Hery (Trunojoyo Madura University, 2025)
The phenomenon of domestic violence that results in the death of women by intimate partners shows a gap in the legal protection that should be provided by the state. This study examines how Law Number 23 of 2004 concerning the Elimination of Domestic Violence (UU PKDRT) regulates and qualifies murder in domestic relations, and the extent of its effectiveness in implementation. The issues discussed include aspects of normative regulation and the application of law in the field. The methodology applied is normative legal research, using a legislative approach and a case approach. Data sources were obtained through literature studies from laws and regulations, court decisions, and relevant academic opinions, and analyzed qualitatively. The findings show that although the Law on PKDRT contains legal provisions regarding serious physical violence, including that which causes death, its implementation has not been optimal. The low understanding of law enforcement officers, the influence of patriarchal culture, and the lack of protection for victims are the main obstacles. Therefore, integration between the Criminal Code and the Law on PKDRT is needed, as well as increasing the competence of law enforcement officers so that victim protection becomes more effective and just.